PENGUATAN KARAKTER LEADERSHIP BERBASIS KEARIFAN LOKAL DALAM BUKU CERITA SUKU PENUNGGANG LAYANG-LAYANG KARYA TERE LIYE - Ridlo, Fauzan; Ningsih, Tutuk (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Moral degradation as a form of weak character is not new among society. More and more cases are occurring due to the fading of karaker values. Character planting should be done as early as possible in order for the nation's successor to be a superior successor. Basically setiaap idividu have character and carry it, it's just necessary strengthening to strengthen it. The purpose of this research is to examine the strengthening of leadership character or leadership based on local wisdom contained in Tere Liye's children's storybook entitled Suku Penunggang Layang-Layang published by Gramedia. This type of research is a library research or research ustaka. Where data is obtained from a number of reading sources and references. The results of this research show that the strengthening of leadership character or leadership based on local wisdom is shown by tetukong or the main character of the story must face conflict between himself and his ability to ride a kite. Anxiety and pressure is what makes Tetukong finally dare to make a decision. Until finally Tetukong was determined to dare to ride a kite and with his belief he was finally able to ride the kite. And finally the story ends with Tetukong being the leader of the kite rider to the fire site.Keyword: strengthening character, leadership, based on local wisdom